2020
DOI: 10.1038/s41598-020-73821-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-time on-machine observations close to interelectrode gap in a tool-based hybrid laser-electrochemical micromachining process

Abstract: A tool-based hybrid laser-electrochemical micromachining process involves concurrent application of two process energies i.e. electrochemical and laser in the same machining zone by means of a hybrid tool which serves as an ECM tool as well as a multimode waveguide. It is a relatively novel process finding applications in defect-free machining of difficult-to-cut materials without affecting their microstructure. In order to understand the physical phenomena occurring during this process, in-situ observations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Jiang et al [136] subsequently applied the system to create Ni-Co-SiC deposits with enhanced mechanical and corrosion properties and substrate adhesion (0.8 A/cm 2 , 0.5 T). The authors observed a (111) crystallographic texture, which was enhanced when depositing from higher SiC concentration electrolytes. This was associated with the greater deposition of Co 2+ , which is reported to interact more strongly with SiC than Ni 2+ .…”
Section: Magnetic-assist Ejpmentioning
confidence: 97%
See 3 more Smart Citations
“…Jiang et al [136] subsequently applied the system to create Ni-Co-SiC deposits with enhanced mechanical and corrosion properties and substrate adhesion (0.8 A/cm 2 , 0.5 T). The authors observed a (111) crystallographic texture, which was enhanced when depositing from higher SiC concentration electrolytes. This was associated with the greater deposition of Co 2+ , which is reported to interact more strongly with SiC than Ni 2+ .…”
Section: Magnetic-assist Ejpmentioning
confidence: 97%
“…Generated gases and debris will delocalise and attenuate the laser in an unpredictable manner, which challenges appropriate focussing [111]; this also complicates translational milling. Therefore, alignment is generally undertaken manually prior to EJM, and the laser will drift or become unfocussed upon material removal.…”
Section: Iv)mentioning
confidence: 99%
See 2 more Smart Citations
“…They measured the time at which the electrolyte starts boiling under different parameter settings. Saxena et al [16] employed large scale particle image velocimetry (PIV) to understand the transportation and flow velocities during ECM process which was subsequently followed in the work of Tchoupe et al [17] where PIV was applied in conjunction with dynamic similarity (scaling of IEG) to understand the transport of gas bubbles in ECM. Rommes et al [18] applied PIV in conjunction with laser sheet to understand gas transport over a larger processing area.…”
Section: Introductionmentioning
confidence: 99%